It Is Not Just the FEV1 That Matters, but the Personal Goals We Reach Along the Way: Qualitative, Multicenter, Prospective, Observational Study - Martinus C Oppelaar; Lara S van den Wijngaart; Peter J F M Merkus; Ellen A Croonen; Cindy A C Hugen; Marianne L Brouwer; Annemie L M Boehmer; Jolt Roukema (JMIR Publications, 2021)
BackgroundThe COVID-19 pandemic has boosted the use of forced expiratory volume in 1 second (FEV1) telemonitoring in pediatric asthma, but a consensus on its most efficient and effective implementation is still lacking. To find answers, it is important to study how such an intervention is perceived, experienced, and used by both patients and health care professionals (HCPs). ObjectiveThe aim of this study was to provide perspectives on how FEV1 home monitoring should be used in pediatric asthma. MethodsThis is a qualitative, multicenter, prospective, observational study which included patients with asthma aged 6-16 and HCPs. Primary outcomes were results of 2 surveys that were sent to all participants at study start and after 3-4 months. Secondary outcomes consisted of FEV1 device usage during 4 months after receiving the FEV1 device. ResultsA total of 39 participants (26 patients and 13 HCPs) were included in this study. Survey response rates were 97% (38/39) at the start and 87% (34/39) at the end of the study. Both patients and HCPs were receptive toward online FEV1 home monitoring and found it contributive to asthma control, self-management, and disease perception. The main concerns were about reliability of the FEV1 device and validity of home-performed lung function maneuvers. FEV1 devices were used with a median frequency of 7.5 (IQR 3.3-25.5) during the 4-month study period. ConclusionsPatients and HCPs are receptive toward online FEV1 home monitoring. Frequency of measurements varied largely among individuals, yet perceived benefits remained similar. This emphasizes that online FEV1 home monitoring strategies should be used as a means to reach individual goals, rather than being a goal on their own.